2016
DOI: 10.1007/s12665-016-6069-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of channel lateral migration rates in the Inner Mongolian reach of the upper Yellow River

Abstract: Channel variations of the Inner Mongolian reach in the upper Yellow River are very complicated because of diversity of channel patterns, intense changes in water and sediment, and enhanced human activities in the last decades. It is important to examine the channel migration rates in this river reach. Based on channel planform changes at 236 digital channel cross-sections, the present study estimated the channel migration rates in terms of mid-channel line shift at the digital channel cross-sections during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, in the case of Sajó River, this state was just temporary and then gently started to increase again. The main fact could be related to the poorly constructed protection works that sometimes just only reduce the effects in a short-term period, which can easily evolve later again (Surian 1999;Wang et al, 2016;Yousefi et al, 2016). Regarding the modified reaches overlapping the natural ones, as the modified R11 and the intensely modified R8, the main driving factors are now not the erosion rates but the planform variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of Sajó River, this state was just temporary and then gently started to increase again. The main fact could be related to the poorly constructed protection works that sometimes just only reduce the effects in a short-term period, which can easily evolve later again (Surian 1999;Wang et al, 2016;Yousefi et al, 2016). Regarding the modified reaches overlapping the natural ones, as the modified R11 and the intensely modified R8, the main driving factors are now not the erosion rates but the planform variables.…”
Section: Discussionmentioning
confidence: 99%
“…However, detailed quantification may be difficult to perform if we compare their content to recent cartographic or aerial datasets due to the considerable differences among scales (Li et al, 2007). The majority of studies worldwide focusing on planform channel changes are composed on the basis of military and later on civil aerial imagery from the early 1940's (Michalková et al, 2010;Nicoll and Hickin 2010;Yousefi et al, 2017;Hajdukiewicz and Wyżga 2019), topographic maps of various dates (Sarma et al, 2007;Yao et al, 2013) or even satellite imagery (Wang et al, 2014(Wang et al, , 2016Yousefi et al, 2016). Classic photogrammetric methods were used as a quick method for generating maps from aerial and terrestrial photographs (Pyle et al, 1997;Hughes et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The rivers systems play an important role to mobilize the environment and ecological balance of specific regions ( Arsenault et al., 2015 ). The river bank shifting are the main geomorphological process of a fluvial system ( Wang et al., 2016 ). The bank shifting of river can be considered as the result of the change of the water flow of the river and over many years the river is having drastic shifting of its banks ( Best et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Li et al [13] calculated the migration widths and intensities of channel thalweg at both section-and reach-scales in the braided reach in 1986-2015, and it was found that thalweg-migration width and intensity at reach-scale were reduced, respectively, by 47% and 35% after the initial operation of the reservoir in 1999. However, these traditional methods using a limited number of historical maps or cross-sectional topography are generally localized in extent, and hence cannot accurately investigate the detailed channel migration processes of alluvial rivers [20][21][22].…”
Section: Introductionmentioning
confidence: 99%